Chemical Characterization of Marine Aerosols in a South Mediterranean Coastal Area Located in Bou Ismaïl, Algeria - Sidali Khedidji; Konrad Müller; Lyes Rabhi; Gerald Spindler; Khanneh Wadinga Fomba; Dominik van Pinxteren; Noureddine Yassaa; Hartmut Herrmann (Aerosol and Air Quality Research)
Abstract Daily concentrations of inorganic and organic compounds associated with PM10, i.e., atmospheric particulate matter with aerodynamic diameter of less than 10 µm, was determined at the south Mediterranean coastal area located in Bou Ismaïl, 40 km west of the Algiers city area in Algeria. From September 2011 to January 2012, chemical characterization of aerosol particles comprising water-soluble ions (WSI), trace metals, carbonaceous aerosols, the anhydrosugars levoglucosan and arabitol, dicarboxylic acids, and semi-volatile organic compounds (SVOC), i.e., alkanes, PAHs, and hopanes, was carried out by using a variety of analytical techniques. Overall, the concentrationrace metals, carbonaceous aerosols, the anhydrosugars levoglucosan and arabitol, dicarboxylic acids, and semi-volatile organic coms of selected ionic species were similar to those reported at other Mediterranean sites, ranging from 3.62 µg m−3 to 5.20 µg m−3 for the monthly total WSI. Sulfate was the most abundant ion. The total concentrations of semi-volatile organic compounds (SVOC) recorded in Bou Ismaïl ranged from 7.06 to 58.8 ng m−3 for n-alkanes, from 2.44 to 35.3 ng m−3 for polycyclic aromatic hydrocarbons (PAHs), from 0.14 to 1 ng m−3 for hopanes, and from 0.67 to 13.2 ng m−3 for n-alkan-2-one. In order to reconcile species concentrations and their emission sources, sampling days were grouped into two categories according to air mass origin. In the first group, the aerosol particles were mainly of a marine origin, while those of the second group originated in the dust sector. A source analysis of total contents organic compounds (PAHs, alkanes, hopanes, and alkanones) and individual inorganic compounds by spearman rank correlation illustrated that the principal sources consisted of sea salt, secondary aerosol, and biomass burning. Additionally, PM10 constituent diagnostic ratios and the carbon preference index (CPI) for n-alkanes indicated the importance of anthropogenic emissions.